Implementing Quality Culture at SD Negeri 2 Kaliaman: A Case Study in Kembang District - Rustamto Rustamto; Yovitha Yuliejantiningsih; Muhammad Prayito (Journal of Educational Sciences, 2026)
Education quality is strongly influenced by the culture of quality within schools, which shapes collaboration, trust, and academic achievement among school members. This study aims to examine the implementation of quality culture at SD Negeri 2 Kaliaman, Kembang District, Jepara, focusing on three key elements: reliability culture, trust culture, and academic optimism. A qualitative case study approach was employed, with data collected through interviews, observations, and documentation to obtain an in-depth understanding of the strategies and practices used to develop quality culture. The findings indicate that the school has effectively fostered a culture of reliability through structured supervision, teacher motivation, and competency enhancement via training and the use of technology. Trust culture has strengthened communication and cooperation among teachers, students, and the community, while academic optimism is demonstrated through collaborative academic and non-academic activities involving teachers, students, and parents. However, challenges remain, particularly in fully integrating technology into teaching practices and bridging gaps in understanding between parents and the school. In conclusion, implementing a quality culture plays a critical role in improving educational outcomes, promoting stakeholder engagement, and creating a sustainable and competitive learning environment.